Robekan Perineum pada Persalinan Vaginal di Bidan Praktik Swasta (BPS) Daerah Istimewa Yogyakarta Indonesia Tahun 2014-2016 - Nuring Pangastuti (JURNAL KESEHATAN REPRODUKSI, 2016)
Background: Vaginal delivery is the most preffered mode of delivery by all women, and the birth attendants. The vaginal delivery assistance was conducted by various health professionals such as midwives, physicians, and obstetricians. Various complaints of pelvic floor dysfunction and complaints related to the perineum as a result of vaginal perineal laceration during childbirth can affect the quality of life of a woman.Objective: To identify and conduct an analysis of maternal factors (maternal age, parity, gestational age), fetal factor (birth weight), and the labor factor (duration of 2nd stage of labor), with the occurrence of perineal rupture in vaginal delivery at the 5 Midwife’s Private Clinic (MPC), Yogyakarta, Indonesia.Method: Retrospective medical record searching, from January 2014 until December 2016.Result and Discussion: There were 1595 obtained samples of data that met the criteria for inclusion and exclusion. Number of perineal laceration reached 1201 (75.3%), with 1.9% of them are grade 3. Perineal rupture occurred in 80.55% of vaginal deliveries at young age, 69.14% in more than 35 years old women, and 85.05% primiparas. There was significant negative correlation (0.186) between parity and perineal rupture (p=0.000). The less the parity, the higher the incidence of perineal rupture (p=0.002). There was significant correlation between baby’s weight less than 2500 gram and perineal rupture but not for the baby’s weight more than 4000grams (p=0.304). The correlation was positive which meant that the heavier the baby’s weight the higher the incidence of perineal rupture. There was significant positive correlation (p=0,018) for the duration of 2nd stage of labor between 30-60 minutes and perineal rupture(0.061). The correlation was positive as well (0.092) for the duration of 2nd stage of labor more than 60 minutes and perineal rupture( p=0.002). The longer the duration of the 2nd stage of labor the higher the incidence of perineal rupture.Conclusion: There was significant relationship between parity, and duration of the 2nd stage of labor and perineal rupture in vaginal delivery.Keywords: perineal rupture, vaginal delivery, parity, duration of the 2nd stage of labor